MASK AS AN OBJECT OF ARTISTIC RESEARCH IN CHINA: EXPERIENCE OF METHODOLOGICAL SYNTHESIS - СЯНЬ, ХУ (Art and Design, 2022)
The aim of the article is to form the theoretical and methodological foundations of the study of the Beijing Opera mask on the basis of the analyzed historiography and source base, as well as on the basis of systematization of own expeditions, interviews, etc. Methodology. The study contains a cross-cutting method and the integration of many disciplines, such as artistic anthropology, ethnology and sociology, history and archeology, semiotics. The methodology used is based on the research paradigms of historicism, structuralism, realism. Results. The study focuses on historical and modern masks of Chinese Beijing Opera. For art studies of the functioning of the mask in the Chinese theater, the existing methods and methodologies of studying the Chinese art of masks are analyzed in depth. A complex scientific approach to the research of the ancient and complex folklore phenomenon of the mask is used in order to analyze its forms, color, quality and meaning. It was found that the synthetic research methodology, which is based on comparative art analysis of masks, in particular in the cultures of China, Japan and Europe, allows to study cultural origins, historical development, genre, type of mask modeling, symbolism, artistic characteristics, trends in theater context, folk traditional art, souvenir design, etc. Scientific novelty – the formation of theoretical and methodological foundations for the study of the mask of the Beijing Opera on the basis of analysis of historiography and source base. The practical significance of the study is due to the possibility of using the research results to develop textbooks and programs for in-depth study of Chinese art.